Levetiracetam-induced rage and suicidality: Two case reports and review of literature - Molokwu, Orakwue A. (Epilepsy Behav Case Rep, 2015)
BACKGROUND: Levetiracetam-induced rage is a rare neurobehavioral adverse effect of levetiracetam that is characterized by seething rage, uncontrollable anger, fits of fury, depression, violence, and suicidal tendencies. It occurs more in patients with prior mood or psychotic disturbances. No such case has been reported in Nigeria. METHOD: We report two cases of levetiracetam-induced rage. The first patient was a 29-year-old male with a 14-year history of intractable posttraumatic epilepsy. He was initially placed on sodium valproate and phenobarbitone and later had phenobarbitone replaced with levetiracetam. Within the first week of initiating levetiracetam, he became aggressive, bursted into fits of fury, and attacked his siblings. Levetiracetam was stopped, and the seething rage ceased only to reappear when it was reintroduced; hence, the complete withdrawal of levetiracetam. Naranjo probability score for adverse drug reaction was 8. RESULTS: The second patient was a 23-year-old lady who developed seething rage and made several attempts to kill herself with a knife following addition of levetiracetam to the clonazepam and carbamazepine that she was taking for treatment-resistant epilepsy. Withdrawal and reintroduction of levetiracetam by the relatives led to cessation and reemergence, respectively, of the rage and suicidal tendencies. Naranjo score was 8. Levetiracetam was discontinued. CONCLUSION: Neuropsychiatric evaluation for prior mood or psychiatric disorders in those initiating levetiracetam therapy is suggested alongside monitoring for early features of levetiracetam-induced rage by both caregivers and physicians. This will help stem the morbidity and potential mortality associated with this life-threatening adverse drug reaction.